IgA anti-beta2-glycoprotein I autoantibodies are associated with an increased risk of thromboembolic events in patients with systemic lupus erythematosus. - Nadera J Sweiss (Public Library of Science (PLoS), 2010)
Background The clinical utility of testing for antiphospholipid antibodies (aPL) of IgA isotype remains controversial. Methodology/principal findings To address this issue, we reasoned that if IgA aPL contribute to the clinical manifestations of the antiphospholipid syndrome, then an association with thromboembolic events should manifest in patients whose only aPL is of IgA isotype. We performed a retrospective chart review of 56 patients (31 with systemic lupus erythematosus [SLE] and 25 without SLE) whose only positive aPL was IgA anti-beta2-glycoprotein I (isolated IgA anti-beta2GPI) and compared their clinical features with 56 individually matched control patients without any aPL. Patients with isolated IgA anti-beta2GPI had a significantly increased number of thromboembolic events, as compared to controls. When patients were stratified into those with and without SLE, the association between isolated IgA anti-beta2GPI and thromboembolic events persisted for patients with SLE, but was lost for those without SLE. Titers of IgA anti-beta2GPI were significantly higher in SLE patients who suffered a thromboembolic event. Among patients with isolated IgA anti-beta2GPI, there was an increased prevalence of diseases or morbidities involving organs of mucosal immunity (i.e., gastrointestinal system, pulmonary system, and skin). Conclusions/significance The presence of isolated IgA anti-beta2GPI is associated with an increased risk of thromboembolic events, especially among patients with SLE. IgA anti-beta2GPI is associated with an increased prevalence of morbidities involving organs of mucosal immunity.